Features of α‐HBDH in COVID‐19 patients: A cohort study. Issue 1 (29th December 2020) - Zhu, Haoming; Qu, Gaojing; Yu, Hui; Huang, Guoxin; Chen, Lei; Zhang, Meiling; Wan, Shanshan; Pei, Bin
Abstract: Background: Coronavirus disease‐2019 (COVID‐19) has spread all over the world and brought extremely huge losses. At present, there is a lack of study to systematically analyze the features of hydroxybutyrate dehydrogenase (α‐HBDH) in COVID‐19 patients. Methods: Electronic medical records including demographics, clinical manifestation, α‐HBDH results and outcomes of all included patients were extracted. Results: α‐HBDH in COVID‐19 group was higher than that in excluded group ( p  < 0.001), and there was no significant difference in α‐HBDH before and after the exclusion of 5 patients with comorbidity in heart or kidney ( p  = 0.671). In COVID‐19 group, the α‐HBDH value in ≥61 years old group, severe group, and critical group, death group all increased at first and then decreased, while no obvious changes were observed in other groups. And there were significant differences of the α‐HBDH value among different age groups ( p  < 0.001), clinical type groups ( p  < 0.001), and outcome groups ( p  < 0.001). The optimal scale regression model showed that α‐HBDH value ( p  < 0.001) and age ( p  < 0.001) were related to clinical type. Conclusions: α‐HBDH was increased in COVID‐19 patients, obviously in ≥61 years old, death and critical group, indicating that patients in these three groups suffer from more serious heart and kidney and other tissues and organs damage, higher α‐HBDH value, and risk of death. The difference between death and survival group in early stage might provide a approach to judge the prognosis. The accuracy of the model to distinguish severe/critical type and other types was 85.84%, suggesting that α‐HBDH could judge the clinical type accurately. Abstract : α‐HBDH was increased in COVID‐19 patients, obviously in ≥61 years old, death, and critical group, indicating that patients in these three groups suffer from more serious tissues and organs damage, higher α‐HBDH value, and risk of death. The obvious difference between death and survival group in early stage may provide an approach to judge the prognosis. The accuracy of the model to distinguish severe/critical type and other types is 85.84%, suggesting that α‐HBDH could judge the clinical type of COVID‐19 patients accurately. In brief, α‐HBDH is an important indicator to judge the severity and prognosis of COVID‐19.